Photo-fermentative hydrogen production in a 4 m3 baffled reactor: Effects of hydraulic retention time. (September 2017) - Zhang, Quanguo; Lu, Chaoyang; Lee, Duu-Jong; Lee, Yu-Jen; Zhang, Zhiping; Zhou, Xuehua; Hu, Jianjun; Wang, Yi; Jiang, Danping; He, Chao; Zhang, Tian
Highlights: A 4 m 3 pilot-scale baffled continuous-flow photoreactor was established. Photo-H2 was produced from glucose at 30 °C, 3000 lux and 24–72 h HRT. Significant inhomogeneity in medium and performance was noted. Overall H2 production rate was increased with decreasing HRT. Abstract: A 4 m 3 pilot-scale baffled continuous-flow photoreactor with four sequential chambers (#1–#4) was established and tested to evaluate its photo-fermentative hydrogen production from wastewater that contains (10 g/L glucose using a functional consortium at 30 °C, under light with an intensity of 3000 ± 200 lux with a hydraulic retention time (HRT) of 24–72 h. The hydrogen production rate and the broth characteristics varied significantly in the flow direction. The hydrogen production rate was highest in chamber #1, and lower in chambers #2–#4 at an HRT of 72 h, while the peak production rate shifted to the latter chambers as the HRT was shortened. The overall H2 production rate increased as HRT decreased, but was not consistent with the predictions that were based on the complete-mixing assumption.